Hak Gaji Guru Honorer Berdasarkan Aspek Keadilan dan HAM - Maliki Alfajr Davin Chandra Saputra; Shevylia Cahya Ayu Saputri; Dhean Bimantara (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Honorary teachers refer to educators who have not received official appointments as civil servants (PNS) inside formal educational institutions, spanning from primary to secondary education levels. The objective of addressing the issues in this study pertains to the notion of justice and human rights in relation to the pay entitlements of honorary professors. In accordance with the Law on human rights and legal justice, any violation of the law and established human rights standards would be deemed unacceptable. The research methodology employed in this study adopts a normative juridical approach, which entails conducting a comprehensive literature review and analyzing theories, concepts, and legislation relevant to the research problems under investigation. The findings of the study indicate To address this issue, it is imperative to ensure diligent oversight in assessing the responsibilities and performance of educators, so enabling them to get a pay commensurate with their exertions, while maintaining fundamental human rights. The government through the ministry of education culture research technology must be a facilitator and directly involved in handling, limiting, and minimizing social inequality between a teacher with civil servant status and an ordinary honorary teacher. Because in essence the teacher is a noble profession that must be heeded and placed in a high degree.